Multiple visceral injuries due to exertional abdominal hypertension - Estrugo, Roberto L.; Geninazzi, Héctor; Müller, Gunther (Cirugía del Uruguay, 1979)
A patient presented acute peritonitis and hemoperitoneum, secondary to multiple visceral lesions, caused by abdominal hypertension due to reiterated abrupt effort. Etiology and pathogenic mechanism is discussed. Therapy was successfuI.